Inhibitory potential of Eucheuma denticulatum (N.L.Burman) F.S. Collins & Hervey against selected foodborne pathogens - Magallanes, Judife N.; Lauzon, Roberta D.; Emnace, Ivy C. (Philippine Journal of Science)
"Seaweed is reported to have antimicrobial properties that can possibly prevent the food from microbial invasion and spoilage. Eucheuma denticulatum (N.L.Burman) F.S. Collins & Hervey is a very abundant seaweed in Leyte province, wherein it is a common part of the human diet. The common problem in food handling, especially street food, is the fast rate of spoilage due to improper handling and packaging. One way of preventing the incidence of food infection and intoxication due to improper packaging of food is the use of packaging material that can inhibit microbial growth. "--abstract.